Genetic parameters in Conilon coffee - Ferrão, Romário Gava; Cruz, Cosme Damião; Ferreira, Adésio; Cecon, Paulo Roberto; Ferrão, Maria Amélia Gava; Fonseca, Aymbiré Francisco Almeida da; Caneiro, Pedro Crescêncio de Souza; Silva, Marcia Flores da (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the performance and to obtain the estimates of the genetic and nongenetic parameters in 40 genetic materials of the Conilon coffee breeding program conducted by Incaper, Espírito Santo State, Brazil. Two experiments were conducted in Marilândia and Sooretama counties, ES, in 1996, 1997, 1998, 1999, 2000, 2001 and 2002 crop seasons, and 16 characteristics were evaluated. Initially, the individual variance analysis was yearly accomplished for each locality, based on the average of the plots in a randomized block experimental design. Later, the combined variance analysis was performed. The genotypes showed high genetic variability on most evaluated traits. The high genotypic determination coefficients and the genetic variation coefficients associated to the high productivities and genetic variability indicate the possibility to obtain success in the genetic breeding programs for the different characteristics evaluated in both counties.